Cutaneous Leishmaniasis an Updating Review of Epidemiology, Diagnosis and Control - Rabia Ali Aboud (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Cutaneous leishmaniasis is a neglected tropical disease caused by dermotropic Leishmania species transmitted by sand flies, with a significant global burden. Specific Background: The disease shows diverse clinical manifestations and complex transmission patterns influenced by ecological, immunological, and socioeconomic factors. Knowledge Gap: Despite advances in understanding parasite biology and diagnostic tools, challenges remain in early detection, treatment variability, and access to healthcare in endemic regions. Aims: This review summarizes epidemiology, pathogenesis, diagnosis, treatment, and control strategies of cutaneous leishmaniasis while highlighting key gaps. Results: Findings indicate that disease distribution is shaped by environmental changes, host immune responses determine clinical outcomes, and molecular diagnostics such as PCR provide high sensitivity. Treatment remains limited by toxicity, resistance, and accessibility issues. Novelty: The article integrates multiple dimensions of the disease and emphasizes the relevance of a One Health approach linking human, animal, and environmental health. Implications: Strengthening diagnostic capacity, improving therapeutic strategies, and implementing integrated control measures are essential to reduce disease burden and improve patient outcomes. Keywords: Cutaneous Leishmaniasis, Epidemiology, Diagnosis, Treatment, Vector Control Key Findings Highlights Global transmission patterns are shaped by ecological and socio-environmental changes Immune response dynamics determine disease progression and lesion outcomes Diagnostic and therapeutic limitations remain major barriers in endemic regions